Etika Dan Profesionalisme Saksi Ahli Forensik - Didik Sudyana; Soni Soni (Universitas Muhammadiyah Riau, 2020)
Abstract The Indonesian court system recognizes several legal pieces of evidence in a trial. One of them is an expert statement from an expert witness. In presenting an expert witness in a trial, there must be a requirement that must be met by an expert witness in order to be called an expert witness. In addition, expert witnesses must also have ethics and professionalism in carrying out their duties as an expert witness. This paper will later discuss expert witnesses further, what are the conditions for becoming an expert witness, how the attitude of an expert witness in court, ethics and professionalism of expert witnesses, and then discuss one case example of how an expert witness violated his ethics and professionalism.